1999
DOI: 10.1002/(sici)1097-0193(1999)8:1<1::aid-hbm1>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Impaired somatosensory discrimination of shape in Parkinson's disease: Association with caudate nucleus dopaminergic function

Abstract: Tactile discrimination of macrogeometric objects in a two-alternative forced-choice procedure represents a demanding task involving somatosensory pathways and higher cognitive processing. The objects for somatosensory discrimination, i.e., rectangular parallelepipeds differing only in oblongness, were presented in sequential pairs to normal volunteers and 12 parkinsonian patients. The performance of patients was significantly impaired compared to normal volunteers. From a biochemical point of view, the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
(13 reference statements)
2
12
0
Order By: Relevance
“…PD also influences haptic shape perception. Such perception involves sensorimotor pathways and higher cognitive processes, and has been associated with diminished PET imaging of the 6-[18F]-fluoro-L-DOPA tracer in the head of the caudate nucleus [9]. Like more circumscribed measures of spatial discrimination, and unlike PPS thresholds, aberrancies in haptic perception are reportedly attenuated by DRMs [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PD also influences haptic shape perception. Such perception involves sensorimotor pathways and higher cognitive processes, and has been associated with diminished PET imaging of the 6-[18F]-fluoro-L-DOPA tracer in the head of the caudate nucleus [9]. Like more circumscribed measures of spatial discrimination, and unlike PPS thresholds, aberrancies in haptic perception are reportedly attenuated by DRMs [33].…”
Section: Discussionmentioning
confidence: 99%
“…While declines in olfactory and visual function are well documented in PD [3,4], deficits in other sensory systems are less so, and most studies have evaluated medicated PD patients of relatively advanced stage. In the case of somatosensation, PD-related decrements in spatial discrimination [5,6], temporal processing [7,8], and haptic perception [9,10] are reasonably well established. However, this is not the case for point pressure sensitivity (PPS), a measure of myelinated Aβ fiber function mediated through Merkel and Meissner mechanoreceptors [11][12][13].…”
Section: Introductionmentioning
confidence: 93%
“…Despite the intuitive interest in unveiling the relationships between nigrostriatal dysfunction and cognitive performances in PD, the expected prevalence of cognitive correlations with nigro‐caudate than with nigro‐putaminal function has been reported by some authors,7–10 but not confirmed by others 11–14. Similar inconsistencies have been found with the relationships between nigro‐putaminal function and motor impairment 9…”
mentioning
confidence: 97%
“…Some methodological and technical limitations could account for these conflicting results, as reviewed recently 6. In the quoted studies, the majority of patients were on levodopa ( L ‐dopa) therapy for a long time7, 9, 12 or had a long disease duration, ranging from a mean of about 412, 15 to 15 years 9. Moreover, some studies included patients with PD dementia (PDD)9 whereas in others, the findings were not compared with those from a control group 8, 16.…”
mentioning
confidence: 99%
“…A role for nigrostriatal dysfunction in PD‐related cognitive deficits has been suggested in several studies using both PET scans with [18F] and SPECT DAT scans . Most of this evidence suggests correlations between nigrocaudate function and cognitive performance, mainly executive tasks in patients with PD at different stages of disease .…”
Section: Middle/advanced Phasementioning
confidence: 99%